Phase behavior in multicomponent mixtures - Sturtewagen, Luka; Dewi, Belinda P. C.; Bot, Arjen; Venema, Paul; van der Linden, Erik (Frontiers in Soft Matter, 2024)
We study the phase behavior of two polydisperse hydrocolloids, dextran and polyethylene oxide. We combine data on the experimental osmometric virial coefficients of the pure components with the experimental critical point of their aqueous mixture and the size distribution of each component from a previously published study in order to predict the phase boundary, spinodal and fractionation upon demixing of the polydisperse mixture. We compare the results of our calculation to the experimental phase diagram. Our method reveals a better correspondence with the experimental binary phase behavior compared to modelling each component as monodisperse. The polydispersity of the hydrocolloids causes the phase separation boundary to shift to lower concentrations and the miscibility region to decrease, and change its shape from a rotated U-shape to a W-shape.